Collection of triatomines from sylvatic habitats by a Trypanosoma cruzi-infected scent detection dog in Texas, USA. - Devin M Christopher; Rachel Curtis-Robles; Gabriel L Hamer; Justin Bejcek; Ashley B Saunders; Walter D Roachell; Thomas Leo Cropper; Sarah A Hamer (Public Library of Science (PLoS), 2023)
Background Triatomine insects, vectors of the etiologic agent of Chagas disease (Trypanosoma cruzi), are challenging to locate in sylvatic habitats. Collection techniques used in the United States often rely on methods to intercept seasonally dispersing adults or on community scientists' encounters. Neither method is suited for detecting nest habitats likely to harbor triatomines, which is important for vector surveillance and control. Furthermore, manual inspection of suspected harborages is difficult and unlikely to reveal novel locations and host associations. Similar to a team that used a trained dog to detect sylvatic triatomines in Paraguay, we worked with a trained scent detection dog to detect triatomines in sylvatic locations across Texas. Principle methodology/findings Ziza, a 3-year-old German Shorthaired Pointer previously naturally infected with T. cruzi, was trained to detect triatomines. Over the course of 6 weeks in the fall of 2017, the dog and her handler searched at 17 sites across Texas. The dog detected 60 triatomines at 6 sites; an additional 50 triatomines were contemporaneously collected at 1 of these sites and 2 additional sites without the assistance of the dog. Approximately 0.98 triatomines per hour were found when only humans were conducting searches; when working with the dog, approximately 1.71 triatomines per hour were found. In total, 3 adults and 107 nymphs of four species (Triatoma gerstaeckeri, Triatoma protracta, Triatoma sanguisuga, and Triatoma indictiva) were collected. PCR testing of a subset revealed T. cruzi infection, including DTUs TcI and TcIV, in 27% of nymphs (n = 103) and 66% of adults (n = 3). Bloodmeal analysis of a subset of triatomines (n = 5) revealed feeding on Virginia opossum (Didelphis virginiana), Southern plains woodrat (Neotoma micropus), and eastern cottontail (Sylvilagus floridanus). Conclusion/significance A trained scent detection dog enhanced triatomine detections in sylvatic habitats. This approach is effective at detecting nidicolous triatomines. Control of sylvatic sources of triatomines is challenging, but this new knowledge of specific sylvatic habitats and key hosts may reveal opportunities for novel vector control methods to block the transmission of T. cruzi to humans and domestic animals.